Within‐individual leaf allometry and the evolution of leaf morphology: A multilevel analysis of leaf allometry in temperate Viburnum (Adoxaceae) species. Issue 5 (15th August 2022) - Strelin, Marina M.; Diggle, Pamela K.
Abstract: A critical issue in evolutionary biology is understanding the relationship between macroevolutionary patterns of diversity and the origin of variation at the organismal level. Among‐individual allometry, the relationship between the size and shape of a structure among organisms at a fixed developmental stage, is often similar to evolutionary allometry, the relationship between the size and shape of a structure among populations or species, and the genetic and developmental process that underlie allometric relationships at both levels are thought to influence evolutionary diversification. Metameric organisms present an additional level of allometry: the relationship between the size and shape of structures within individuals. We propose that within‐individual allometry is also related to evolutionary diversification among metameric organisms. We explore this idea in temperate deciduous Viburnum (Adoxaceae) species that bear two types of leaves, that is, preformed and neoformed leaves, with contrasting patterns of development. Examination of within‐individual, among‐individual, among‐population, and among‐species allometry of leaf shape in both leaf types showed that the slopes of all allometric relationships were significantly different from isometry, and their sign was consistent across allometric hierarchies. Although the allometric slope of preformed leaves was constant across allometry levels, the allometric slope of neoformed leaves became increasingly steeper. We suggest that allometric variation underlying evolutionary diversification in metameric organisms may manifest among individuals and also among their repeated structures. Moreover, structures with contrasting patterns of development within metameric organisms can experience different degrees of developmental constraint, and this can in turn affect morphological diversification. Abstract : Within‐individual allometry in metameric organisms, that is, the relationship between size and shape among different metamers, may affect evolutionary diversification, as it parallels among‐individual and evolutionary allometries in Viburnum .